Potenciales Evocados Somatosensitivos (PESS) obtenidos por estimulación del nervio Mediano (registros espinal y craneano) en caninos - Pellegrino, F.C. (2005)
We investigated SSEPs in 22 normal dogs of both sexes (12 females), aged between 3 and 14 years (mean: 7 +/- 4 years old) by recording the electrical signal at the spinal cord (L7-S1 and L5-L6) and at the scalp (frontoparietal region) in response to median nerve stimulation. Conduction velocity (CV) of median nerve and its roots was calculated, measuring the distance between the stimulating cathode and the recording electrode, and dividing it into the latency of the of the spinal cord arrival corresponding negative peak. Central conduction time (CCT) was estimated subtracting the latencies of the spinal potencial from the cranial potential. We employed needle electrodes sited between C7-T1 and in the scalp, at the contralateral region respect to the stimulus. At the spinal level a triphasic wave was obtained, its first deflection being positive followed by a larger negative potential and ending up with another small positive deflection. The mean latency to the main negative peak was 4.95 ms +/-0.92 ms. The mean value of CV was 60.79 +/-13.53 m/s. Cranial SSEPs had a ?w? shape, their mean latency to the negative peak was 14.62 +/-1.83 ms. The mean value of CCT was 9.67 +/-2.02 ms. In 6 out of the 22 studied dogs, once the regular recording was obtained, the stimulating electrodes were moved distally and a new recording was acquired; this procedure allowed to measure the median nerve conduction velocity between the 1st and the 2nd sites of stimulation, in a restricted segment of the nerve trunk; following this procedure the mean value obtained was 59.83 +/-21.44 m/s, which did not significantly differ from the former calculation. In regards to the sources of these potentials, most probably the spinal one constitute the spatial sum of the electrical activity of the different structures sited in the recording site. The cranial response is brought about by the activation of the thalamo-cortical circuits and the neurons of the parietal cortex situated at the receiving area.